2008
DOI: 10.1136/ard.2008.095919
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive and prognostic study of systemic sclerosis-associated myopathies

Abstract: Muscle histopathology is critical in the therapeutic management of SSc-associated myopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 14 publications
0
76
0
3
Order By: Relevance
“…This treatment, which is usually well tolerated, may be prescribed intravenously at 0.6 gm/m 2 /month for 6 -12 months or orally at 1 mg/kg/day for 1 year. Again, among the many adverse events associated with cyclophosphamide therapy, the risk of infection is increased, particularly in (20,42) and/or skin involvement in patients with dcSSc (43), may result in mouth ulcers, although these ulcers usually occur only in the absence of folic acid treatment. These ulcers generally require local treatment, usually with antiseptic agents.…”
Section: Resultsmentioning
confidence: 99%
“…This treatment, which is usually well tolerated, may be prescribed intravenously at 0.6 gm/m 2 /month for 6 -12 months or orally at 1 mg/kg/day for 1 year. Again, among the many adverse events associated with cyclophosphamide therapy, the risk of infection is increased, particularly in (20,42) and/or skin involvement in patients with dcSSc (43), may result in mouth ulcers, although these ulcers usually occur only in the absence of folic acid treatment. These ulcers generally require local treatment, usually with antiseptic agents.…”
Section: Resultsmentioning
confidence: 99%
“…Skeletal muscle disease in scleroderma is common, with a prevalence of 13-81% depending on the criteria used to define muscle involvement (1)(2)(3)(4)(5)(6)(7). Some studies have defined muscle disease by subjective proximal weakness only, while more rigorous investigations require electromyography and muscle biopsies to define muscle disease (8). One study reported that muscle involvement in scleroderma as a poor prognostic feature impacting survival, especially those of male gender, or early diffuse disease, or interstitial lung disease (9).…”
Section: Introductionmentioning
confidence: 99%
“…The main pathological features of systemic sclerosisassociated myopathies are mononuclear inflammation (63%), muscle atrophy (60%), necrosis (59%), regeneration (44%), fibrosis (24%), and microangiopathy (27%). The histological muscle inflammation seemed to be associated with good response to corticosteroids and better muscle prognosis, however myopathy without inflammation such as atrophy and fibrosis might have poor muscle prognosis [15]. Discrimination between myopathy and myositis with systemic sclerosis is clinically important to decide the therapeutic choice, because steroid therapy may be effective for myositis but ineffective for myopathy without inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of muscle involvements in patients with systemic sclerosis varies from 14% to 81% [15]. The main pathological features of systemic sclerosisassociated myopathies are mononuclear inflammation (63%), muscle atrophy (60%), necrosis (59%), regeneration (44%), fibrosis (24%), and microangiopathy (27%).…”
Section: Discussionmentioning
confidence: 99%